2014
DOI: 10.4103/0974-1208.138872
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of subendometrial-endometrial blood flow assessment by two-dimensional power Doppler with pregnancy outcome in frozen-thawed embryo transfer cycles

Abstract: CONTEXT:Various markers have been proposed to evaluate endometrial receptivity, such as molecular markers and sonographic markers. Commonly used sonographic markers include endometrial thickness and pattern. A good endometrial blood flow is considered necessary for improved pregnancy outcome.AIM:The aim of the present study is to evaluate the role of subendometrial endometrial blood flow with two-dimensional-power Doppler (2D-PD) in predicting pregnancy outcome in hormone replacement frozen-thawed embryo trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
2
33
1
2
Order By: Relevance
“…24 Divya Sardana et al, suggested that a combination of endometrial thickness and Doppler analysis of endometrial blood flow was a simple and effective tool to improve the outcome of IVF/ET and should be incorporated into routine clinical practice. 25 This was suggested by our study results in addition to the endometrial pattern.…”
Section: Discussionsupporting
confidence: 48%
“…24 Divya Sardana et al, suggested that a combination of endometrial thickness and Doppler analysis of endometrial blood flow was a simple and effective tool to improve the outcome of IVF/ET and should be incorporated into routine clinical practice. 25 This was suggested by our study results in addition to the endometrial pattern.…”
Section: Discussionsupporting
confidence: 48%
“…Usually, the PI of the uterine artery, early diastolic notch, and end‐diastolic blood flow are used to evaluate ER; however, these measures reflect the blood flow in the whole uterus. In fact, the blood flow surrounding the implantation site is of greater importance for embryo implantation . A reduction in endometrial vascularity has been observed in women with unexplained infertility .…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective clinical study Kim et al [51] demonstrated that three-dimensional-power Doppler ultrasound (3D-PD-US) was useful for evaluating endometrial and subendometrial neo-vascularization in intrauterine insemination cycle. A recent prospective study confirmed that the presence of subendometrial-endometrial blood flow improved cycle outcome in frozen-thawed embryo transfer cycles [52]. The clinical studies suggest that 3D-PD-US can be used to monitor during induced ovulatory cycles the stage of progesterone response by the presence and extent of subendometrialendometrial blood flow.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 90%